Cardioprotective strategies are not “one size fi ts all”. Is it time to consider personalised medicine? - Lecour, Sandrine; Hadebe, Nkanyiso; Opie, Lionel (SA Heart Journal, 2017)
Since the discovery of the conditioning phenomenon in 1986 (whereby brief episodes of ischaemia reperfusion protect against a sustained ischaemic insult), thousands of preclinical studies have explored the benefits and signaling mechanisms of this cardioprotective strategy which aims to protect patients undergoing percutaneous coronary interventions (PCI), or cardiopulmonary bypass (CPB) surgery, against ischaemia reperfusion injury. A large number of proof of concept clinical trials have highlighted the benefits of conditioning to protect patients against ischaemia reperfusion injury, but none have yet translated to the clinical routine. The outcomes of the multicenter studies ERICCA,(1) RIPHeart(2) and CIRCUS(3) which involved larger number of patients (1 612, 1 385 and 970 respectively) were eagerly awaited, hoping that pharmacological conditioning with cyclosporine A, or remote ischaemic preconditioning, could soon become part of the clinical routine.